2023
DOI: 10.3390/app13031251
|View full text |Cite
|
Sign up to set email alerts
|

Trust Components: An Analysis in The Development of Type 2 Diabetic Mellitus Mobile Application

Abstract: Trust in information and communication technology devices is an important factor, considering the role of technology in carrying out supporting tasks in everyday human activities. The level of trust in technology will influence its application and adoption. Recognizing the importance of trust in technology, researchers in this study will examine trust components for the development of a type 2 diabetes mobile application. The results of this study resulted in three major focuses, namely the application design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…[ 9 , 10 ] However, web-based programs are often underutilized in diabetes management, and previous studies have focused more on medication adherence than self-management education. [ 11 , 12 , 13 , 14 , 15 ] There are even fewer published studies covering the impact of mobile app-based trials, and most interventions have examined the effect of short messages on adherence to treatment in diabetic patients. [ 16 ] Additionally, none of the 25 interventions included in the previously mentioned systematic review reported a positive effect on all DSMES components (the seven self-care behaviors), and there was no significant change in health-related quality of life in another systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 ] However, web-based programs are often underutilized in diabetes management, and previous studies have focused more on medication adherence than self-management education. [ 11 , 12 , 13 , 14 , 15 ] There are even fewer published studies covering the impact of mobile app-based trials, and most interventions have examined the effect of short messages on adherence to treatment in diabetic patients. [ 16 ] Additionally, none of the 25 interventions included in the previously mentioned systematic review reported a positive effect on all DSMES components (the seven self-care behaviors), and there was no significant change in health-related quality of life in another systematic review.…”
Section: Introductionmentioning
confidence: 99%